2010
DOI: 10.1111/j.1755-148x.2010.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental melanoma models in fish

Abstract: Experimental animal models are extremely valuable for the study of human diseases, especially those with underlying genetic components. The exploitation of various animal models, from fruitflies to mice, has led to major advances in our understanding of the etiologies of many diseases, including cancer. Cutaneous malignant melanoma is a form of cancer for which both environmental insult (i.e., UV) and hereditary predisposition are major causative factors. Fish melanoma models have been used in studies of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 201 publications
(322 reference statements)
0
60
0
Order By: Relevance
“…To improve our understanding of the environmental components of UV exposure and skin cancer, several animal models have been employed including mouse (Merlino and Noonan, 2003), the South American opossum (Kusewitt et al, 1991) and Xiphophorus fishes (Walter and Kazianis, 2001). Of these model organisms, Xiphophorus fishes have been shown to be a particularly valuable model to assess UVB-induced DNA damage, DNA repair, and induced melanomagenesis (Nairn et al, 2001; David et al, 2004; Patton et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…To improve our understanding of the environmental components of UV exposure and skin cancer, several animal models have been employed including mouse (Merlino and Noonan, 2003), the South American opossum (Kusewitt et al, 1991) and Xiphophorus fishes (Walter and Kazianis, 2001). Of these model organisms, Xiphophorus fishes have been shown to be a particularly valuable model to assess UVB-induced DNA damage, DNA repair, and induced melanomagenesis (Nairn et al, 2001; David et al, 2004; Patton et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In spite of these added complexities, many of the same genes and control networks found in mammals are conserved in fish [4], [5]; and considering their small size and easy manipulation, fish are suitable models for a better understanding of vertebrate pigmentation. Indeed, fish have been used as models for melanoma research because it has been shown tissues within fish share molecular signatures and histopathological features with human cancers [6]. The genetics of pigmentation have been explored in several model teleost fish including zebrafish [7], [8], medaka [9], fugu [10], goldfish [11], [12] and, recently, in flatfish [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…In all, 25 out of the 183 animals developed exophytic lesions before beginning the adult acute irradiations. We believe that these animals represent the background melanoma frequency for the Sp- couchianus BC model that is due to the genetic predisposition of BC Xiphophorus fishes (for review see Patton et al 2010). In support of this, the observed frequency was not significantly different from that of non-irradiated Sp- couchianus BC animals (25 TBF out of 183 individuals, melanoma frequency = 13.7%; published background frequency: 40 TBF out of 216 individuals, melanoma frequency = 18.5%; χ 2 =1.71, P =0.19).…”
Section: Resultsmentioning
confidence: 99%
“…The viability and fertility of hybrid animals in this system provides a powerful classical genetics approach for revealing the determinants of melanomagenesis (Nairn et al, 2001; Meierjohann and Schartl, 2006; Mitchell et al, 2007). The investigation of more than 20 hybrid crosses has led to the realization that hybrid strains have different susceptibilities to carcinogens (chemical, UV) and spontaneous rates of melanoma formation (Patton et al, 2010). Despite these differences, melanomas in Xiphophorus always result from the overexpression of a receptor tyrosine kinase ( Xiphophorus melanoma receptor kinase, Xmrk ) that is a mutated derivative of the fish ortholog for the human epidermal growth factor receptor (EGFR/ErbB-1).…”
Section: Introductionmentioning
confidence: 99%